Optimization of Process Variables by Response Surface Methodology - Ravinder, Kashipeta (International Journal of Applied Sciences and Biotechnology, 2015)
In the present study optimisation of the growth medium for the production of Cyclodextrin glucanotransferase (CGTase) was carried out using response surface methodology. Four important parameters namely starch, yeast extract, K2HPO4 and MgSO4 concentrations were selected as the independent variables and the enzyme activity (CGTase activity U/mL) was the dependent response variable. Each of these independent variables was studied at five different levels as per central composite design (CCD) in four variables with a total of 28 experimental runs. The optimal calculated values of tested variables for maximal production of CGTase were found to be comprised of: starch, 2.16 %; yeast extract, 0.6 %; K2HPO4, 0.62 %; MgSO4, 0.04 % with a predicted CGTase activity of 150 U/ml. These predicted optimal parameters were tested in the laboratory and the final CGTase activity obtained was very close to the predicted value at 148.2 U/ml. Int J Appl Sci Biotechnol, Vol 3(4): 592-598